Razumevanje jezika i verbalno pamćenje kod starijih osoba - Paunović, Verica; Vuković, Mile (Specijalna edukacija i rehabilitacija, 2025)
Introduction. In normal aging, certain language and cognitive functions may decline. Objective. The aim of this paper was to determine the ability of language comprehension and verbal memory in older people with normal aging. Method. The sample consisted of 50 respondents divided into three groups. The first two groups included older respondents. One group consisted of 19 respondents aged 66 to 75, while the other group included 15 respondents aged 76 to 85. The control group consisted of 16 respondents aged 30 to 60. The Token Test (TT) was used to assess language comprehension, and the Ray Auditory Verbal Memory Test (RAVLT) assessed verbal memory. Results. Elderly respondents aged 76 to 85 years were significantly worse on the TT compared to those aged 66 to 75 years (U = 79.50) and the control group (U = 50.50). Both groups of older respondents were significantly worse on all five repetitions of the RAVLT word list compared to the control group. Also, the younger group of elderly respondents (66-75 years old) achieved better scores on the first four repetitions of the word list compared to the older group (76- 85 years old). No statistically significant correlation was found between achievement on the TT and the RAVLT in any group of older respondents. Conclusion. Elderly people showed a decline in language comprehension and verbal memory. The decline is more prominent with ageing.
Keywords: elderly people; physiological aging; language comprehension; verbal memory